Essential Engagement as the First Step in Gaining Entrée into the Laotian American Community on Cervical Cancer Screening - Catherine Pravisay-Malmstadt; Connie K. Y. Nguyen-Truong (JMIR Publications, 2020)
Asian American women, including Laotian American women (LAW), have the lowest rate of being up to date with cervical cancer (CC) screenings at 75% compared to other ethnic groups (85% White, 86% Black, 79% Hispanic, 79% American Indian/Alaska Native; American Cancer Society, 2019; Nghiem, Davies, Chan, Mulla, & Cantor, 2016). This rate is substantially lower than the national objective of 93% (Healthy People.gov, 2020). CC is highly treatable if caught early in the localized stage with a 91.8% 5-year survival rate (National Cancer Institute, n.d.). There is scant research on the incidence and factors surrounding CC screening in Laotian Americans and has primarily been representative of California. The Portland metropolitan area in the United States' (U.S.) Pacific Northwest has one of the top ten highest Laotian American populations (Greblo, 2011). The Laotian American cultural community leaders (CCLs) in the Pacific Northwest expressed to our academic project team at Washington State University Elson S. Floyd College of Medicine and the College of Nursing that the Laotian American community is a private ethnic group wary of those from the outside and particularly researchers. Research evidence points to the importance of meaningful stakeholder engagement in scholarly work (Bourassa et al., 2020; Dill et al., 2020; Hoekstra et al., 2020; 1Nguyen-Truong, 1Fritz et al., 2018; Nguyen-Truong, Tang, & Hsiao, 2017; Wallenstein, Duran, Oetzel, & Minkler, 2018). The purpose of this brief article is to describe the first essential engagement step of relationship building between the academic project team and Laotian American CCLs to gain entrée to the Laotian American community regarding a sensitive topic on gynecologic health.